What Is a Good Rank? The Effort and Performance Effects of Adding Performance Category Labels to Relative Performance Information* - Knauer, Thorsten; Sommer, Friedrich; Wöhrmann, Arnt (Contemporary Accounting Research, 2021)
ABSTRACT Prior research demonstrates that relative performance information affects effort and performance. However, little is known about the qualitative design parameters of these information systems. This study examines, via an experiment, how adding performance category labels to ranks (e.g., “good” ranking position and “poor” ranking position) affects effort and performance. Furthermore, we investigate the effort and performance effects of two design choices observed in practice: the type of performance category labels and the proportion of positively labeled ranks. We argue that performance category labels motivate greater effort and performance through competition for status, which varies with both the type of performance category labels and the proportion of positively labeled ranks. We find partial support for our hypothesis that adding performance category labels increases effort and performance. Specifically, we find positive effects if top ranks are positively labeled and bottom ranks are negatively labeled (combined labels) but not if only top ranks are labeled (positive‐only labels). We also find as predicted that the positive effects on effort resulting from using combined labels, instead of positive‐only labels, are stronger when the proportion of positively labeled ranks is larger. The results for performance are weaker. Our results shed new light on the usefulness of performance category labels and emphasize how firms can render relative performance information more effective.